Efficacy of Hi-Lo Evac Endotracheal Tube in Prevention of Ventilator-Associated Pneumonia in Mechanically Ventilated Poisoned Patients - Ahmad Ghoochani Khorasani; Shahin Shadnia; Mohammad Mashayekhian; Mitra Rahimi; Abbas Aghabiklooei (Scientifica)
Background. Ventilator-associated pneumonia (VAP) is the most common health care-associated infection. To prevent this complication, aspiration of subglottic secretions using Hi-Lo Evac endotracheal tube (Evac ETT) is a recommended intervention. However, there are some reports on Evac ETT dysfunction. We aimed to compare the incidence of VAP (per ventilated patients) in severely ill poisoned patients who were intubated using Evac ETT versus conventional endotracheal tubes (C-ETT) in our toxicology ICU. Materials and Methods. In this clinical randomized trial, 91 eligible patients with an expected duration of mechanical ventilation of more than 48 hours were recruited and randomly assigned into two groups: (1) subglottic secretion drainage (SSD) group who were intubated by Evac ETT (n=43) and (2) control group who were intubated by C-ETT (n=48). Results. Of the 91 eligible patients, 56 (61.5%) were male. VAP was detected in 24 of 43 (55.8%) patients in the case group and 23 of 48 (47.9%) patients in the control group (P=0.45). The most frequently isolated microorganisms were S. aureus (54.10%) and Acinetobacter spp. (19.68%). The incidence of VAP and ICU length of stay were not significantly different between the two groups, but duration of intubation was statistically different and was longer in the SSD group. Mortality rate was less in SSD group but without a significant difference (P=0.68). Conclusion. The SSD procedure was performed intermittently with one-hour intervals using 10 mL syringe. Subglottic secretion drainage does not significantly reduce the incidence of VAP in patients receiving MV. This strategy appears to be ineffective in preventing VAP among ICU patients.